Simulation of resource-conserving technologies on productivity, income and greenhouse gas GHG emission in rice-wheat system - Saharawat, Yashpal S.; Ladha, Jagdish Kumar; Pathak, Himanshu; Gathala M; Chaudhary, N.; Jat, Mangi Lal (Academic Journals, 2012)
The Rice-wheat (RW) cropping system is one of the major agricultural production systems in four Indo-Gangetic Plains (IGP) countries: India, Pakistan, Bangladesh and Nepal of South Asia covering about 32% of the total rice area and 42% of the total wheat area. The excessive utilization of natural resource bases and changing climate are leading to the negative yield trend and plateauing of Rice-wheat (RW) system productivity. The conservation agriculture based efficient and environmental friendly alternative tillage and crop establishment practices have been adopted by the farmers on large scale. A few tools have been evolved to simulate the different tillage and crop establishment. In the present study, InfoRCT (Information on Use of Resource Conserving Technologies), a excel based model integrating biophysical, agronomic, and socioeconomic data to establish input-output relationships related to water, fertilizer, labor, and biocide uses; greenhouse gas (GHG) emissions; biocide residue in soil; and Nitrogen (N) fluxes in the rice-wheat system has been validated for farmer participatory practices. The assessment showed that double no-till system increased the farmer s income, whereas raised-bed systems decreased it compared with the conventional system. The InfoRCT simulated the yield, water-use, net income and biocide residue fairly well. The model has potential to provide assessments of various cultural practices under different scenarios of soil, climate, and crop management on a regional scale.